Implementasi Program Keluarga Harapan Sebagai Upaya Penanggulangan Kemiskinan di Kecamatan Berbah Sleman Tahun 2013 - Bakhtiar, Ahmad Nur; Qodir, Zuly (Universitas Muhammadiyah Yogyakarta, 2015)
The study aims to determine the implementation and the factors that play a role in the PKH program conducted in thedistrict Berbah 2013. The research method used is descriptive qualitative research. Data was collected throughinterviews and documentation. The data analysis done by qualitative descriptive. The results showed: 1. Aspects ofcompliance in the implementation of CCT programs in the district Berbah can be seen from: a). PKH implementationrules in the district Berbah besides the rules of the center, are also required to attend group meetings, b). Commitmentto the rule implementing CCT implementation in districts Berbah year 2013 has been very good, c). Implementingcompliance in implementing the phases of activity in the district PKH Berbah in 2013 is good, and 2. Factors that playa role in the implementation of the poverty reduction program (PKH) in the district Berbah in 2013: a). Resource; tosource funds using budget funds I, II budget, and governmental organizations, and to human resources from thedistrict level up to the hamlet level has been good, b). Communication fellow companion if no help each activity, c).Implementing attitude if there are conditions on the ground which is not in accordance with the rules of implementationof the CCT, the immediate improvement to validate the data, d). Socio-economic conditions of communities in thedistrict Berbah fish farmers have had good production, the trade sector has also been improved.